Pengaruh Uang Saku dan Gaya Hidup terhadap Pola Konsumsi Mahasiswa Universitas Nahdlatul Ulama Indonesia - Agustina, Asiroch Yulia; Awnurropiq, Awnurropiq (Mozaic : Islam Nusantara, 2022)
The development of consumption patterns that occur is quite significant but has not been matched by allowance and lifestyle owned by students of the University of Nahdlatul Ulama Indonesia. So that this study aims to determine the effect of pocket money and lifestyle on consumption patterns of students from the Faculty of Economics and Business, Nahdlatul Ulama University, Indonesia. This type of research is quantitative, ie the data obtained in the form of numbers and numeric. The population used is the students of the Faculty of Economics and Business, University of Nahdlatul Ulama Indonesia using a simple random sampling sample with the number of respondents, namely 100 respondents. The results of this study state that H1 is the Tcount value generated on the Allowance variable is 3.252 and Ttable is 1.660 with the results of the analysis (3.252> 0.05) meaning that H1 is accepted, it can be concluded that the money variable has a significant effect on student consumption patterns. H2 That is the Tcount value generated on the Lifestyle variable is 0.656 and Ttable 1.660 with the results of the analysis (0.656> 0.05) meaning that H2 is accepted, it can be concluded that the lifestyle variable has a significant effect on student consumption patterns.